PERGESERAN KESANTUNAN POSITIF SISWA KELAS IX MTs N 1 SURAKARTA BERLATAR BELAKANG BUDAYA JAWA - Noor, Khilyatin Ulin (Universitas Muhammadiyah Surakarta, 2016)
This research aims to describe the pattern of politeness and the shifts ofÂ positive politeness among students of class IX MTs N 1 Surakarta. In addition,this research also aims to identify the factors that are influencing the emergenceÂ of positive politeness shift among those students. This research is classified asÂ descriptive qualitative research. The data includes speech of class IXâs studentsÂ that contains positive politeness. The data collected by taking notes from theÂ studentsâ speech. Data sources are all students of class IX MTs N 1 Surakarta.Â Methods in analysis include the intralingual match methods by comparing theÂ lingual elements with the extra-lingual elements. The results showed that thereÂ are six forms of positive politeness shifts which then lead to the 13 patterns ofÂ positive politeness strategy used by students who have Javanese culture backgrounds.Â Those patterns include attention to the pattern of preferences, desires,Â and the needs of what opponent said; exaggerate things to get attention, approval,Â and sympathy from the opponents; using a marker of group identity; seekingÂ approval to repeat some or all of the speakers utterances; pseudo agreement,Â white lies, hedging opinion; small talk and presuppositions; jokes; expressedÂ understanding or understanding what are the opponent said; making promises;Â show an attitude of optimism; involves the opponents in the activities; ask questionsÂ or give reasons; also reciprocal relationship. In addition, there are severalÂ factors that are influencing positive politeness shifts. They are social distance,Â contexts, excessive complimenting, deliberately asked for a reason, no harm intentions,and rejections.